MAPPING TSUNAMI HAZARD LEVELS IN PACITAN BEACH USING REMOTE SENSING METHODS - Jamilah, Zahrotin; Widodo, Amien; Ariyanti, Nita (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2021)
Pacitan Regency is one of the tourist destinations in East Java due to the beauty of tourism from the caves to the beaches that stretch along the southern part of Pacitan. Apart from tourism potential, Pacitan Regency, which borders the Indian Ocean in the south, has the potential to be hit by a tsunami wave that occurs due to the collision of the Eurasian and Indo-Australian plates. By using a remote sensing method, it can be seen how the tsunami hazard level of an area is based on the parameters of the slope, the height of the area, and the distance from the coastline. In addition, the level of exposure of the population is also a factor in determining the level of tsunami hazard. In Pacitan Regency, the area affected by the low level tsunami reached 33753 Hectare, the medium level was 13498 Hectare, and the high level was 3828 Hectare. Areas with a high level of danger are located along the coast which extends in the southern part of Pacitan Regency. The area with the highest level of danger with a wider coverage is around Pacitan Bay. Therefore, it is necessary to have an appropriate mitigation system in reducing the risk of tsunamis, especially around the coast which is used as a tourist destination.